Cognitive-Behavioral Therapists’ Experience on Relevance of Sleep and Sleep Disorders in Training and Clinical Practice: A Survey Study from Italy - Chiara Baglioni; Andrea Galbiati; Debora Meneo; Greta Cavadini; Francesca Gelfo; Francesco Mancini; Carlo Buonanno (Brain Sciences)
Background/Objectives: Based on previous data reporting the status of health professionals’ training about sleep clinical psychophysiology, insomnia, and its treatment in the US and Canada, this paper aims at providing a snapshot of the Italian situation, considering health professionals qualified to offer cognitive behavioral therapy (CBT). Adding information on different countries is important, as national health systems differ significantly, and distinct evidence-based pathways for change may be proposed. Methods: Two hundred and thirteen CBT professionals (180 females; 33 males) answered a 5 min survey about their training and experience in recognizing and treating behavioral sleep disorders in their practice. The questionnaire was diffused through the mailing list of the Italian Behavioral and Cognitive Therapy Society (Società Italiana di Terapia Comportamentale e Cognitiva, SITCC) throughout December 2023 and January 2024. Results: A total of 213 participants completed the survey. Only a minor proportion of respondents (37.1%) reported having received training for diagnosis and treatment of insomnia or other behavioral sleep disorders. Familiarity with psychological therapeutics for sleep was mainly associated with knowledge of sleep hygiene rules, relaxation, and mindfulness techniques, but not with core CBT strategies for insomnia (i.e., sleep restriction and stimulus control) and sleep regulation. The less familiar therapeutics were those for pediatric insomnia. Conclusions: The results of this study highlight scarce knowledge and consideration of sleep problems in CBT practice in Italy. As insomnia is prevalent, an independent mental disorder, and a predictor for mental and somatic comorbid conditions, these findings underscore an urgency to enlarge and strengthen CBT professionals’ training on sleep psychophysiology, sleep clinical psychology, insomnia, behavioral sleep problems, and their treatment.